Diffusing Risk and Building Resilience through Innovation: Reciprocal Exchange Relationships, Livelihood Vulnerability and Food Security amongst Smallholder Farmers in Papua New Guinea - Koczberski, G.; Curry, George; Bue, V.; Germis, E.; Nake, S.; Tilden, G. (2018)
This paper examines how oil palm migrant farmers in Papua New Guinea are responding to shortages of land for food gardening. Despite rapid population growth and planting nearly all of their land to oil palm, virtually all families continue to grow sufficient food for their families. The paper outlines the diverse range of adaptive strategies that households have employed to maintain food security, involving both intensification and innovation in farming systems. While gains from intensification have been significant and built resilience, they have been incremental, whereas innovation has been transformative and led to large gains in resilience. The adoption of more flexible land access arrangements on state leasehold land that ‘revive’ and adapt indigenous systems of land sharing and exchange that operated through kinship networks on customary land are innovative; they have increased the supply of land for food gardening thereby reducing risk for individual households and the broader smallholder community. The paper highlights the value of understanding farmer-driven innovations and the role of indigenous institutions and cultural values in sustaining and enhancing household food security.